Utilization Of Cook Fish Flour (Channa striata) In Making Fish Crackers - Alkhamdan, Taufik; Husain, Rahim (Universitas Negeri Gorontalo, 2022)
This study aims to determine the organoleptic quality of fish crackers substituted with snakehead fish meal (channa striata), and to determine the chemical quality of fish crackers. The method used was different concentrations of snakehead fish meal (0g, 85g, 75g, 65g) in the process of making crackers, hedonic analysis and chemical analysis. The results of this study cork fish crackers (Channa striata) gave a significantly different effect on appearance, taste, aroma and did not give a significantly different effect on color and texture. The selected product was treatment B (75g:100g) with proximate content, namely 3.96% water content, 1% ash content, 5.9% protein content, 3.18% fat content, 82.76% carbohydrate content and cracker albumin content. Snakehead fish is worth 0.51% while the albumin content of snakehead fish meal is 0.72%.